Pollen tube tip growth depends on plasma membrane polarization mediated by tobacco PLC3 activity and endocytic membrane recycling - Helling, Diana; Possart, Anja; Cottier, Stéphanie; Klahre, Ulrich; Kost, Benedikt (The plant cell, 2006)
Phosphatidyl inositol 4,5-bisphosphate (PI 4,5-P2) accumulates in a Rac/Rop-dependent manner in the pollen tube tip plasma membrane, where it may control actin organization and membrane traffic. PI 4,5-P2 is hydrolyzed by phospholipase C (PLC) activity to the signaling molecules inositol 1,4,5-trisphosphate and diacyl glycerol (DAG). To investigate PLC activity during tip growth, we cloned Nt PLC3, specifically expressed in tobacco (Nicotiana tabacum) pollen tubes. Recombinant Nt PLC3 displayed Ca2+-dependent PI 4,5-P2-hydrolyzing activity sensitive to U-73122 and to mutations in the active site. Nt PLC3 overexpression, but not that of inactive mutants, inhibited pollen tube growth. Yellow fluorescent protein (YFP) fused to Nt PLC3, or to its EF and C2 domains, accumulated laterally at the pollen tube tip plasma membrane in a pattern complementary to the distribution of PI 4,5-P2. The DAG marker Cys1:YFP displayed a similar intracellular localization as PI 4,5-P2. Blocking endocytic membrane recycling affected the intracellular distribution of DAG but not of PI 4,5-P2. U-73122 at low micromolar concentrations inhibited and partially depolarized pollen tube growth, caused PI 4,5-P2 spreading at the apex, and abolished DAG membrane accumulation. We show that Nt PLC3 is targeted by its EF and C2 domains to the plasma membrane laterally at the pollen tube tip and that it maintains, together with endocytic membrane recycling, an apical domain enriched in PI 4,5-P2 and DAG required for polar cell growth.